A study of the expansion trends in single-detached row houses - Sobremesana, Rodrigo L.; Florendo, Raquel Baltazar (1989.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Row houses -- Philippines